2020
DOI: 10.1038/s41598-020-60492-7
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: Clinical Implications of Sub-grouping HER2 Positive Tumors by Amplicon Structure and Co-amplified Genes

Abstract: An amendment to this paper has been published and can be accessed via a link at the top of the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Despite the potentially radical surgical treatment of cancer with the appointment of modern chemotherapy and/or radiation therapy, in 40% of patients there is a refund of the disease [18]. The results of 2 randomized studies of various variants of organ-breaching treatment have shown that in patients receiving combined treatment (operation + radiation therapy + chemotherapy), the frequency of local recurrences ranged from 0.3% to 8%, while after only the operations local recurrence ranged from 10% to 34% [19,20].…”
mentioning
confidence: 99%
“…Despite the potentially radical surgical treatment of cancer with the appointment of modern chemotherapy and/or radiation therapy, in 40% of patients there is a refund of the disease [18]. The results of 2 randomized studies of various variants of organ-breaching treatment have shown that in patients receiving combined treatment (operation + radiation therapy + chemotherapy), the frequency of local recurrences ranged from 0.3% to 8%, while after only the operations local recurrence ranged from 10% to 34% [19,20].…”
mentioning
confidence: 99%